Nodos: Encyclopedia of the Performing Arts - Torres, Diego (2017)
The main goal of Nodos is to promote the collective creation of semantic knowledge regarding performing arts. Recording and curating information about these expressions contributes to the preservation of the Intangible Cultural Heritage, as defined by UNESCO. One of the challenges related to the preservation of information is the large amount of people involved in the creation and development of scenic arts and the dynamism in these theater pieces. The large number of plays presented every year makes it difficult to keep records up to date, resulting in the loss of knowledge about many cultural pieces. This article introduces a way to record such cultural heritage in the context of a citizen science project. Nodos defines an ontology regarding performing arts and also uses a semantic wiki that helps in the implementation of the ontology. An evaluation of usability shows Nodos as an effective initiative to preserve and study performing arts.